Effect of Music on Branding Effectiveness : An Experimental Study of Telecom Brands - Bagdare, Shilpa; Bansal, Pooja (Indian Journal of Marketing, 2014)
Music, as a powerful sensory stimulus, is effectively used by marketers for a variety of purposes ranging from advertising, events, websites, and products to retailing. In the recent past, its use as a brand communication element has gained greater momentum due to information overload. Studies have examined the impact of music on consumer perceptions, attitudes, emotions, engagement, and other behavioural responses. Experimental studies have studied the effect of music in the retailing and advertising context. The present research is an experimental study to investigate the effect of music on branding effectiveness for six telecom brands in India. The results show a significant positive effect (of music) on telecom brands. The study also suggests that music has a differential effect on brands, which differs with regard to brand effectiveness on measurement parameters. The study contributes to the literature on music and branding, and proposes implications for research and practice.